2018
DOI: 10.1265/jjh.73.388
|View full text |Cite
|
Sign up to set email alerts
|

Association between Job Stress and Number of Physical Symptoms among Female Nurses of Medical-university-affiliated Hospitals

Abstract: Objectives: To clarify the association between job stress and the number of physical symptoms among newly certified female nurses. Methods: In this cross-sectional self-administered survey, we investigated 313 female nurses working at three medical-university-affiliated hospitals in February 2016. We investigated working conditions including numbers of working and on-call hours, work-life balance, Job Content Questionnaire (JCQ) scores, and 16 physical symptoms perceived more often than once a week. Results: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Lewandowska et al [7] showed that the most common physical symptoms of burnout include fatigue and exhaustion (79%) and back pain (57%). Similar results were obtained in the study of Yoshioka et al [8], where the nursing staff listed the most common physical complaints: fatigability (66.1%), followed by back pain (44.7%). Ogińska et al [9] also pointed out that the most frequently reported complaints by nurses include back pain (95.5%).…”
Section: Discussionsupporting
confidence: 89%
“…Lewandowska et al [7] showed that the most common physical symptoms of burnout include fatigue and exhaustion (79%) and back pain (57%). Similar results were obtained in the study of Yoshioka et al [8], where the nursing staff listed the most common physical complaints: fatigability (66.1%), followed by back pain (44.7%). Ogińska et al [9] also pointed out that the most frequently reported complaints by nurses include back pain (95.5%).…”
Section: Discussionsupporting
confidence: 89%
“…The multiple linear regression analysis of fatigue score illustrated that physical condition was the influencing factor of fatigue, and both in the 2 dimensions of physical and mental fatigue ( P < .01) (Table 4 ), which was consistent with the result of a previous study that reported people in good physical condition are in less fatigue. [ 31 ] The nurses in emergency department do not merely handle high-intensity work during the daytime, but also work in long-term night shift mode, which would lead to the disturbance of the circadian rhythm of the human body, and result in insomnia, fatigue and other symptoms. [ 32 ] In addition, some research reported that the prevalence rate of various diseases, such as hypertension, anxiety and depression, nurses in emergency department was higher than the nurses in the ward.…”
Section: Discussionmentioning
confidence: 99%
“…9 Among nurses, research in Taiwan showed that about 17% of nurses were categorized in the "high job strain" group (eg, high job demand and low control). 10 The components of job strain (eg, high demand, low control and low levels of social support) were associated with lower well-being, 11 higher physical symptoms, 12 higher stress-related symptoms, 13 higher catecholamine excretion and higher blood pressure more than other workers in different occupation. 14 In addition, continuing to work despite such physical/psychological reactions was correlated with supervisor support among the nurses with high strain.…”
Section: Introductionmentioning
confidence: 99%